Metode Eksperimen: Upaya Meningkatkan Keterampilan Proses Sains Pada Kelompok B2 RA Masyithoh X Karangmojo Gunungkidul - Kinanti, Adha; Purnama, Sigit; Rohinah, Rohinah (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2020)
Learning at RA Masyithoh X Karangmojo is still fixed on the teacher as the center so that children's interactions in the learning process are still lacking and the scientific process skills possessed by the child are still abstract. This research is a classroom action research with 31 subjects of B2 RA Masyithoh X Karangmojo Gunungkidul children. The study was conducted in 2 cycles. Each cycle consists of 4 stages, namely planning, implementing, observing, and reflecting. Data collection methods in this study used observation sheet guides and interview sheets. Data analysis techniques using qualitative data and quantitative data. Success criteria in improving children's science process skills through the application of experimental methods are 80% of the number of children. The results showed: 1) the results of science process skills before taking action in either category are 0% of the number of children; 2) the application of the experimental method is proven to be able to improve the science process skills of the first cycle The application of the experimental method falls into the sufficient category (C) then the application of the experimental method in the second cycle belongs to either category (B); 3) the improvement of science process skills respectively in cycle I and cycle II reached the good category (B), in cycle I action increased to 38.71% of the number of children, so that there was an increase in before cycle I action amounted to 38.71% and cycle II reached the good and very good categories of 93.54% of the number of children, an increase of 54.83% from the actions of cycle I to cycle II.